Differential effects of 3,5-T2 and T3 on the gill regeneration and metamorphosis of the Ambystoma mexicanum (axolotl) - Lazcano, I.; Olvera, A.; Pech-Pool, S. M.; Sachs, L.; Buisine, N.; Orozco, A. (Frontiers in Endocrinology, 2023)
Thyroid hormones (TH) regulate tissue remodeling processes during early- and post-embryonic stages in vertebrates. The Mexican axolotl (Ambystoma mexicanum) is a neotenic species that has lost the ability to undergo metamorphosis; however, it can be artificially induced by exogenous administration of thyroxine (T4) and 3,3´,5-triiodo-L-thyronine (T3). Another TH derivative with demonstrated biological effects in fish and mammals is 3,5-diiodo-L-thyronine (3,5-T2). Since the effects of this bioactive TH remains unexplored in other vertebrates, we hypothesized that it could be biologically active in amphibians and therefore could induce metamorphosis in axolotl. We performed a 3,5-T2 treatment by immersion and observed that the secondary gills were retracted, similar to the onset stage phenotype; however, tissue regeneration was observed after treatment withdrawal. In contrast, T4 and T3 immersion equimolar treatments, as well as a 4-fold increase in 3´5-T2 concentration triggered complete metamorphosis. In order to identify the possible molecular mechanisms that could explain the contrasting reversible or irreversible effects of 3,5-T2 and T3 upon gill retraction, we performed a transcriptomic analysis of differential expression genes in the gills of controls, 3,5-T2- and T3-treated axolotls. We found that both THs modify gene expression patterns. T3 regulates ten times more genes than 3,5-T2, suggesting that the latter has a lower affinity for thyroid hormone receptors (TR) or that these hormones could act through different TR isoforms. However, both TH treatments regulated different gene sets known to participate in tissue development and cell cycle processes. In conclusion, 3,5-T2 is a bioactive iodothyronine which promoted partial gill retraction but induced full metamorphosis in higher concentrations. Differential effects on gill retraction after 3,5,-T2 or T3 treatment could be explained by the activation of different clusters of genes related with apoptosis, regeneration and proliferation; in addition, these effects could be initially mediated by thyroid hormone receptors that are expressed in gills. This study showed for the first time 3,5,-T2 bioactivity in an neotenic amphibian.